Correctional populations in the United States, 1997 (Correctional Populations in the United States)
Presents data on the growing number of persons in the United States under some form of correctional supervision in 1997. Data are drawn from annual BJS surveys and include jurisdiction-level counts of prisoners, probationers, and parolees by sex, race, Hispanic origin, admission type, release type, and sentence length. Data are also provided on persons held in U.S. military confinement facilities and incarcerated persons in U.S. commonwealths and territories. A special chapter on the 1997 Survey of Inmates in State and Federal Correctional Facilities describes inmates in terms of their demographics, current offense, time served, criminal history, drug or alcohol use, and substance abuse treatment. The chapter also compares State and Federal inmates in 1997 with those in 1991.